2019
DOI: 10.1186/s13018-019-1162-5
|View full text |Cite
|
Sign up to set email alerts
|

Reduction and functional outcome of open reduction plate fixation versus minimally invasive reduction with percutaneous screw fixation for displaced calcaneus fracture: a retrospective study

Abstract: Background Minimally invasive surgery has become popular because of the lower incidence of wound complications. However, achieving an anatomic reduction that provides a satisfactory outcome is difficult using minimally invasive surgery. Our study aimed to evaluate the reduction and clinical outcomes of closed reduction and percutaneous fixation treatment using a closed reduction traction device for displaced intra-articular calcaneal fractures compared with traditional open reduction plate fixatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 29 publications
2
15
0
1
Order By: Relevance
“…Complication rates are known to be high ranging from 17.3 to 29% in the literature [ 24 , 27 ]. Recent studies show lower complication rates with minimally invasive techniques compared to open reduction and internal fixation over an extensile lateral approach (4.8% vs. 20.8%) [ 28 ]. In our study, we found an overall complication rate of 29%.…”
Section: Discussionmentioning
confidence: 99%
“…Complication rates are known to be high ranging from 17.3 to 29% in the literature [ 24 , 27 ]. Recent studies show lower complication rates with minimally invasive techniques compared to open reduction and internal fixation over an extensile lateral approach (4.8% vs. 20.8%) [ 28 ]. In our study, we found an overall complication rate of 29%.…”
Section: Discussionmentioning
confidence: 99%
“…Автори [17] зробили аналіз лікування 40 пацієнтів (45 стоп) із переломами п'яткової кістки (2012-2016 рр.). Групу фіксації відкритої репозиції за допомогою пластини (24 стопи) порівнювали з групою закритої репозиції та черезшкірної фіксації (21 стопа) за допомогою тягового пристрою.…”
Section: обговоренняunclassified
“…Many doctors prefer to use minimally invasive surgery to treat freshly closed calcaneal fracture [1,2]. In this procedure, the surgeon often performs closed reduction of the fracture or open reduction with a small incision, in conjunction with percutaneous fixation [3]. This has many advantages compared to open reduction internal fixation (ORIF) [4,5] including fewer incision-related complications [6], shorter duration of limb swelling [7], shorter recovery time [8], and lower rate of fixation failure [9].…”
Section: Introductionmentioning
confidence: 99%